Essays in honor of Joon Y. Park : econometric methodology in empirical applications - Chang, Yoosoon; Lee, Sokbae; Miller, J. Isaac (Advances in econometrics, 2023)
Volumes 45a and 45b of Advances in Econometrics honor Professor Joon Y. Park, who has made numerous and substantive contributions to the field of econometrics over a career spanning four decades since the 1980s and counting. This second volume, Essays in Honor of Joon Y. Park: Econometric Methodology in Empirical Applications, focuses on econometric applications related, some closely and some very loosely, to Professor Park's more recent work before concluding with a retrospective summarizing four decades of Advances in Econometrics.